Ginástica laboral, música e estados de ânimo - Bergamaschi, Elaine Cristina [UNESP] (2003)
The present study was developed with 112 participants (workers of both sex) of a pharmaceutical industry. Trying to find the best methodological adjustment, this study was divided in two. Experiment 1 has had as purpose to select accordingly to the participants preference, 3 music of each musical style pre determined - Brazilian rock, dance pop and new age. This music selection was used in experiment 2 that has had purpose to verify the interference of Fitness Employee (G.L.) accompanied or not of different musical styles on collaborator's mood. In this experiment, workers participated of 4 experimental sessions in which they practiced G.L. during 10 minutes accompanied or not of different styles. To verify the results, the LEA-RI (Lista de Estados de Ânimo - Reduzida e Ilustrada) was applied before and after each experimental session. Through a Qualitative Analyses, a Binomial Analyses and a Correspondence Analyses on data, no significant changes in mood states were found. This may be occurred despite to workers familiarity to the sessions they have been practicing for 3 years. Concluding, the G.L. accompanied or not by different music styles did not promoted significant changes in workers mood that already have got a good intensity level of their moods contributing to a good quality of life